2017
DOI: 10.1002/cam4.1137
|View full text |Cite
|
Sign up to set email alerts
|

Cytoreductive nephrectomy for metastatic renal cell carcinoma: inequities in access exist despite improved survival

Abstract: The use of cytoreductive nephrectomy (CRN) in the targeted therapy era is still debated. We aimed to determine factors associated with reduced use of CRN and determine the effect of CRN on overall survival in patients with metastatic renal cell carcinoma (RCC). All advanced RCC diagnosed between 2001 and 2009 in New South Wales, Australia, were identified from the Central Cancer Registry. Records of treatment and death were electronically linked. Follow‐up was to the end of 2011. Multivariable logistic regress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 18 publications
(26 reference statements)
1
9
0
Order By: Relevance
“…Another randomized study, the SURTIME trial, showed that deferred nephrectomy after three cycles of sunitinib had relatively longer OS than immediate nephrectomy (32.4 vs 15.0 months), because more patients received sunitinib in the deferred nephrectomy group 17 . Furthermore, a number of retrospective studies showed the benefit of cytoreductive nephrectomy, including the present study 12,13,15,18–21 . Thus, cytoreductive nephrectomy is still expected to prolong survival, especially in patients with systemic therapy and long survival expectancy, so that the appropriate patient selection for nephrectomy is warranted.…”
Section: Discussionmentioning
confidence: 63%
“…Another randomized study, the SURTIME trial, showed that deferred nephrectomy after three cycles of sunitinib had relatively longer OS than immediate nephrectomy (32.4 vs 15.0 months), because more patients received sunitinib in the deferred nephrectomy group 17 . Furthermore, a number of retrospective studies showed the benefit of cytoreductive nephrectomy, including the present study 12,13,15,18–21 . Thus, cytoreductive nephrectomy is still expected to prolong survival, especially in patients with systemic therapy and long survival expectancy, so that the appropriate patient selection for nephrectomy is warranted.…”
Section: Discussionmentioning
confidence: 63%
“…Rampersaud et al, reported that females <59-year-old presented a better overall survival in comparison to males, suggesting a role for the hormones in RCC development [160]. Surprisingly, in metastatic RCC patients, female sex had a significant independent association with death (HR 1.19) [137]. Mancini et al, reported that disease recurrence seems not to be different among males and females, with the latter showing a more favorable prognosis after recurrence [105].…”
Section: Discussionmentioning
confidence: 99%
“…Such sex disparity seems to be particularly evident among African-American females [136]. Similarly, in the setting of metastatic RCC, Patel et al, found that females were less likely to undergo a cytoreductive nephrectomy as compared to their male counterparts [137]. In a population-based cohort study using data from the National Cancer Database, females with localized renal masses were treated more aggressively than males, with consequent significantly higher risks of overtreatment [138].…”
Section: Treatmentmentioning
confidence: 99%
“…18 This phenomenon is not limited to the USA, as a population-based study in New South Wales noted a 91% decreased likelihood of undergoing CN if a patient was not privately insured. 19 Race may also play a role in treatment selection and access to care, as evidenced by a previous NCDB analysis identifying African American race as an independent risk factor for decreased survival, even in the targeted therapy era. 7 Our analysis elucidates this relationship further, and identifies several racial and socioeconomic risk factors associated with a patient receiving NT.…”
Section: Discussionmentioning
confidence: 99%